Different patterns of nuclear and mitochondrial penetration by the G3 PAMAM dendrimer and its biotin–pyridoxal bioconjugate BC-PAMAM in normal and cancer cells in vitro - Uram, Łukasz (Int J Nanomedicine, 2015)
The intracellular localization and colocalization of a fluorescently labeled G3 amine-terminated cationic polyamidoamine (PAMAM) dendrimer and its biotin–pyridoxal (BC-PAMAM) bioconjugate were investigated in a concentration-dependent manner in normal human fibroblast (BJ) and squamous epithelial carcinoma (SCC-15) cell lines. After 24 hours treatment, both cell lines revealed different patterns of intracellular dendrimer accumulation depending on their cytotoxic effects. Cancer cells exhibited much higher (20-fold) tolerance for native PAMAM treatment than fibroblasts, whereas BC-PAMAM was significantly toxic only for fibroblasts at 50 µM concentration. Fibroblasts accumulated the native and bioconjugated dendrimers in a concentration-dependent manner at nontoxic range of concentration, with significantly lower bioconjugate loading. After reaching the cytotoxicity level, fluorescein isothiocyanate-PAMAM accumulation remains at high, comparable level. In cancer cells, native PAMAM loading at higher, but not cytotoxic concentrations, was kept at constant level with a sharp increase at toxic concentration. Mander’s coefficient calculated for fibroblasts and cancer cells confirmed more efficient native PAMAM penetration as compared to BC-PAMAM. Significant differences in nuclear dendrimer penetration were observed for both cell lines. In cancer cells, PAMAM signals amounted to ~25%–35% of the total nuclei area at all investigated concentrations, with lower level (15%–25%) observed for BC-PAMAM. In fibroblasts, the dendrimer nuclear signal amounted to 15% at nontoxic and up to 70% at toxic concentrations, whereas BC-PAMAM remained at a lower concentration-dependent level (0.3%–20%). Mitochondrial localization of PAMAM and BC-PAMAM revealed similar patterns in both cell lines, depending on the extracellular dendrimer concentration, and presented significantly lower signals from BC-PAMAM, which correlated well with the cytotoxicity.